A Proposal for Value-Based Managed Entry Agreements in an Environment of Technological Change and Economic Challenge for Publicly Funded Healthcare Systems - Xoxi, Entela; Rumi, Filippo; Kanavos, Panos; Dauben, Hans-Peter; Gutierrez-Ibarluzea, Iñaki; Wong, Olivier; Rasi, Guido; Cicchetti, Americo (Frontiers in Medical Technology, 2022)
Managed entry agreements (MEA) represent one of the main topics of discussion between the European National Payers Authorities. Several initiatives on the subject have been organized over the past few years and the scientific literature is full of publications on the subject. There is currently little international sharing of information between payers, mainly as a result of the confidentiality issues. There are potential benefits from the mutual sharing of information, both about the existence of MEAs and on the outcomes and results. The importance of involving all the players in the decision-making process on market access for a medicinal product (MP) is that it may help to make new therapies available to patients in a shorter time. The aim of this project is to propose a new pathway of value-based MEA (VBMEA), based on the analysis of the current Italian pricing and reimbursement framework. This requires elaboration of a transparent appraisal and MEA details with at least a 24-month contract. The price of the MP is therefore valued based on the analysis of the VBMEA registries of the Italian Medicines Agency. Although the proposal focuses on the Italian context, a similar approach could also be adapted in other nations, considering the particularities of the single health technology assessment (HTA)/payer system.